Ultrasound-Assisted Wittig Reaction for the Synthesis of 3-Substituted 4-Chloroquinolines and Quinolin-4(1H)-ones with Extended π-Conjugated Systems - Wahiba Frites; Massaab Khalfaoui; Lamouri Hammal; Vera L. M. Silva; Artur M. S. Silva (Journal of Chemistry)
3-(Vinyl-/buta-1,3-dien-1-yl/4-phenylbuta-1,3-dien-1-yl)-4-chloro quinolines and quinolin-4(1H)-ones were synthesized by ultrasound-assisted Wittig reaction of the corresponding 4-chloro-3-formylquinoline and 3-formylquinolin-4(1H)-ones with nonstabilized ylides. Ease execution, mild conditions, and high yields make this method exploitable for the generation of libraries of 3-substituted 4-chloroquinolines and quinolin-4(1H)-ones with extended π-conjugated systems. To demonstrate the usefulness of these compounds as precursors for the synthesis of more complex structures, 3-vinylquinolin-4(1H)-ones were used as dienes in the Diels–Alder reaction with N-methylmaleimide to produce novel acridone derivatives. The attempted Diels–Alder reaction with 3-(buta-1,3-dien-1-yl)quinolin-4(1H)-one did not afford the expected cycloadduct; instead, 2-methyl-2H-pyrano[3,2-c]quinoline was obtained. The structures and stereochemistry of the new compounds were established by NMR studies.